Transient Semi Circular Lid Driven Cavity Flow Using Non Uniform Structured Grid Method with Upwind Scheme - M. S., Idris; N. M. M., Ammar; Tuan Mohammad Yusoff, Tuan Ya; At-Tasneem, Mohd Amin (Faculty Mechanical Engineering, UMP, 2013)
In this article, two dimensional lid driven cavity flow in semi circular cavity is simulated using non uniform finite different method with structured grid. Navier-Stokes and continuity equations are simplified using non dimensional streamfunction-vorticity approach. Reynolds number of 1000 is used and the vorticity and Streamfunction contour plot is monitored with convergence criteria of 1x10-7 set to both vorticity and streamfunction value. The result shows primary vortex move from the upper left cavity corner to the upper right corner while the magnitude of streamfunction grows at the primary vortex centre. The primary vortex size decrease steadily as the time increased. This phenomenon greatly affected by the increasing size of the secondary at the lower left. Slight changes of vortex size are observed as the flow achieving steady state condition. Validation of the simulation is conducted by comparing previous researches results based on the value of streamfunction and centre location of primary vortex.